1974
DOI: 10.1212/wnl.24.7.640
|View full text |Cite
|
Sign up to set email alerts
|

L‐methionine

Abstract: Article abstractFourteen patients under treatment with levodopa for idiopathic Parkinson's disease were placed on a restricted methionine diet, 0.5 gm daily, for eight days. L-methionine, 1.5 gm three times a day, or placebo (lactose) was administered in a randomized, double-blind technique to seven patients. Seven on the low methionine regimen received placebo and three subjectively improved. Five of seven receiving a high I-methionine intake became worse. One patient exhibited a hypersexual, aggressive behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1975
1975
1997
1997

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The absorption of levodopa across the blood-brain barrier as well as the small intestinal mucosa is governed by stereospecific active transport mechanisms for which other L-amino acids are also substrates (Daniel et al, 1976;Wade et al, 1973). Thus Pearce & Waterbury (1974) demonstrated that L-methionine antagonised the clinical effect of levodopa, and Mena & Cotzias (1975) reported that low-protein diets enhanced its efficacy and reduced the severity of fluctuations. More recently Nutt et al (1984) have investigated the effects of high-protein meals.…”
Section: -Ome Dopamentioning
confidence: 99%
“…The absorption of levodopa across the blood-brain barrier as well as the small intestinal mucosa is governed by stereospecific active transport mechanisms for which other L-amino acids are also substrates (Daniel et al, 1976;Wade et al, 1973). Thus Pearce & Waterbury (1974) demonstrated that L-methionine antagonised the clinical effect of levodopa, and Mena & Cotzias (1975) reported that low-protein diets enhanced its efficacy and reduced the severity of fluctuations. More recently Nutt et al (1984) have investigated the effects of high-protein meals.…”
Section: -Ome Dopamentioning
confidence: 99%
“…Whilst the specific central action of methionine remains obscure, there is evidence that L-DOPA acts as a competitive inhibitor of methionine uptake by nerve endings in homogenates of rat brains (Baldessarini & Karobath, 1972). Furthermore, methionine appears to reverse the clinical effectiveness of L-DOPA in Parkinsonism (Pearce & Waterbury, 1974 …”
Section: Discussionmentioning
confidence: 99%
“…Since S-adenosylmethionine in both brain and adrenal medulla tissue is lowered by levodopa, Pearce et al (1971) studied the effect of methionine in Parkinsonism. Since S-adenosylmethionine in both brain and adrenal medulla tissue is lowered by levodopa, Pearce et al (1971) studied the effect of methionine in Parkinsonism.…”
Section: L-methioninementioning
confidence: 99%